Modification of the Battle to Improve Learning Outcomes in The Game of Rasel Ball Students of Grade IV of SDN 3 Balaesang Tanjung - Iswanto, Iswanto; Rahmah, Rahmah; Rifandy, Arief Aditya; Liloi, Delvi Kristanti (International Journal on Advanced Science, Education, and Religion, 2025)
The purpose of this study is to improve the learning outcomes of baseball games through modified bats for fourth-grade students of SDN 3 Balaesang Tanjung. This study is a classroom action research (CAR), which is one type of research conducted by teachers to improve the quality of learning in the classroom. This study took place at SDN 3 Balaesang Tanjung, Balaesang Tanjung District, Donggala Regency, Central Sulawesi Province and used school yard facilities for the implementation of baseball hitting skills learning using modified baseball bats. Elementary school students of SDN 3 Balaesang Tanjung. The class to be studied is class IV which consists of 17 male students and 11 female students. The total number of research subjects is 28 students. Based on the results of the study regarding classroom action research with the title "Modification of Bats to Improve Baseball Hitting Skills of Fourth-grade Students of SDN 3 Balaesang Tanjung in the 2025/2026 Academic Year", it can be concluded that the application of modified bats can improve students' skills in performing basic baseball hitting techniques. In the first cycle, the learning outcomes showed that the highest score obtained by students was 91.7, the lowest score was 50, and the class average was 75.00. The number of students who achieved mastery of hitting skills was 15 people (53.57%), while 13 students (46.43%) had not achieved mastery. In the second cycle, there was a significant increase. The highest score of students reached 100, the lowest score was 75, and the class average increased to 87.2. The number of students who completed the skill increased to 24 people (85.71%), while only 4 students (14.29%) remained incomplete. Thus, the classical mastery target of 85.00% has been achieved, so it can be concluded that the use of modified bats is effective in improving baseball hitting skills.